Poetry of place : helping students write their worlds - Hermsen, Terry, 1950- (Urbana, IL : National Council of Teachers of English, 2009)
Contains thirty lessons developed by the author to engage students in poetry, and includes activities.
"NCTE Stock Number: 36089"--T.p. verso.
Includes bibliographical references (p. 207-211) and index.
Professional
Keywords: Poetry -- Study and teaching; Poetry -- Study and teaching